Shigella OspF blocks rapid p38-dependent priming of the NAIP–NLRC4 inflammasome - Elizabeth A. Turcotte; Kyungsub Kim; Kevin D. Eislmayr; Lisa Goers; Patrick S. Mitchell; Cammie F. Lesser; Russell E. Vance (Proceedings of the National Academy of Sciences, 2026)
The NAIP–NLRC4 inflammasome senses pathogenic bacteria by recognizing the cytosolic presence of bacterial proteins such as flagellin and type III secretion system (T3SS) subunits. In mice, the NAIP–NLRC4 inflammasome provides robust protection against bacterial pathogens that infect intestinal epithelial cells, including the gastrointestinal pathogen Shigella flexneri . By contrast, humans are highly susceptible to Shigella , despite the ability of human NAIP–NLRC4 to robustly detect Shigella T3SS proteins. Why the NAIP–NLRC4 inflammasome protects mice but not humans against Shigella infection remains unclear. We previously found that human THP-1 cells infected with Shigella lose responsiveness to NAIP–NLRC4 stimuli, while retaining sensitivity to other inflammasome agonists. Using mT3Sf, a “minimal Shigella ” system, to express individual secreted Shigella effector proteins, we found that the OspF effector specifically suppresses NAIP–NLRC4-dependent cell death during infection. OspF was previously characterized as a phosphothreonine lyase that inactivates p38 and ERK MAP kinases. We found that p38 was critical for rapid priming of NAIP–NLRC4 activity, particularly in cells with low NAIP–NLRC4 expression. Overall, our results provide a mechanism by which Shigella evades inflammasome activation in humans, and describe a mechanism for rapid priming of the NAIP–NLRC4 inflammasome.